Contribution of Abu Al-Barakat Al-Baghdadi's Thoughts in the Study of Islamic Philosophy - Ryan Arief Rahman; Allam Setiawan Nugroho; Chandra Dwi Setyo Widodo; Rahmat Ardi Nur Rifa Da’i (al-Afkar, Journal For Islamic Studies, 2024)
This article seeks to evaluate the extent of Abu Al-Barakat Al-Baghdadi's contribution to Islamic philosophy. Al-Baghdadi, a critic of philosophy among scientists, has a marginal role in the history of Islamic philosophy due to his greater recognition in the field of science. This article aims to examine Al-Baghdadi's ideas in Islamic philosophy. Through descriptive and analytical methods, this study concludes that al-Baghdadi made a significant contribution to the advancement of Islamic philosophy. His ideas on God, the human soul, and science became a point of reference for numerous Islamic philosophers of his time. It is worth noting that al-Baghdadi can be regarded as a key figure in the field of Islamic philosophy.